Method for producing sulfide-based solid electrolyte containing Sn

By preparing a uniform Li-Sn-S solution in an organic solvent and performing drying and heating steps, the problem of Sn being difficult to disperse uniformly in the solvent in the prior art is solved, and a sulfide-based solid electrolyte with high yield, low impurities and stable performance is prepared, which is suitable for all-solid lithium-ion batteries.

JP7658281B2Active Publication Date: 2025-04-08MITSUBISHI GAS CHEM CO INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021571154
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-17
Filing Date
2021-01-06
Publication Date
2025-04-08
Estimated Expiration
2041-01-06

AI Technical Summary

Technical Problem

The prior art is difficult to disperse Sn uniformly in the solvent, resulting in difficulty in preparing sulfide-based solid electrolytes with good stability.

Method used

The sulfide-based solid electrolyte is prepared by preparing a homogeneous Li-Sn-S solution in an organic solvent and by drying and heating steps to reduce impurities and improve the stability of the electrolyte.

Benefits of technology

The high yield, low impurity and stable performance of sulfide-based solid electrolyte is achieved, and its application potential in all-solid lithium-ion batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658281000002
    Figure 0007658281000002
  • Figure 0007658281000003
    Figure 0007658281000003
  • Figure 0007658281000004
    Figure 0007658281000004
Patent Text Reader

Abstract

The present invention can provide a method for producing a sulfide solid electrolyte, the method characterized by including: a solution preparation step for preparing a uniform solution that includes at least elemental lithium (Li), elemental tin (Sn), elemental phosphorus (P), and elemental sulfur (S) in an organic solvent; a drying step for removing the organic solvent from the uniform solution to obtain a precursor; and a heat treatment step for heat-treating the precursor to obtain a sulfide solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a sulfide-based solid electrolyte containing Sn. [Background technology]

[0002] In recent years, the demand for lithium-ion secondary batteries has been increasing for applications such as mobile information terminals, mobile electronic devices, electric vehicles, hybrid electric vehicles, and even stationary power storage systems. However, current lithium-ion secondary batteries use flammable organic solvents as electrolytes, and require a strong exterior to prevent the organic solvent from leaking. In addition, there are restrictions on the structure of devices, such as the need to adopt a structure that protects against the risk of electrolyte leakage in the event of an accidental leakage of the electrolyte, in the case of portable personal computers, etc.

[0003] Furthermore, their applications are expanding to mobile objects such as automobiles and airplanes, and large capacity is required for stationary lithium-ion secondary batteries. Under these circumstances, there is a tendency to place more importance on safety than ever before, and efforts are being made to develop all-solid-state lithium-ion secondary batteries that do not use harmful substances such as organic solvents.

[0004] For example, the use of oxides, phosphate compounds, organic polymers, sulfides, and the like as solid electrolytes in all-solid-state lithium ion secondary batteries has been considered. Among these solid electrolytes, sulfides have the characteristics of high ionic conductivity, being relatively soft and easily forming solid-solid interfaces. They are also stable as active materials, and development is underway as a practical solid electrolyte. Among sulfide-based solid electrolytes, sulfide-based solid electrolytes containing Sn are known to have good ionic conductivity and high water resistance, and there are high expectations for their practical use (Non-Patent Document 1).

[0005] Known methods for producing solid electrolytes include those that use a ball mill, a vibration mill, etc. to pulverize raw materials while causing a reaction. Recently, a method for synthesizing solid electrolytes in a solvent has been developed (Patent Document 1). Synthesis in a solvent is highly productive and is therefore expected to be a promising method. Conventional sulfide-based solid electrolytes containing Sn often use SnS2, a sulfide of Sn, as a raw material. However, SnS2 has poor solubility in solvents. Therefore, when synthesizing in a solvent, it is difficult to uniformly disperse Sn in the solid electrolyte during synthesis, and there has been an issue that it is difficult to obtain a solid electrolyte that shows stable performance. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication 2019-169459 [Non-patent literature]

[0007] [Non-Patent Document 1] J.Am.Chem.Soc.2013,135,15694-15697 Summary of the Invention [Problem to be solved by the invention]

[0008] Under these circumstances, it is desired to provide a method for producing a sulfide-based solid electrolyte that is highly productive, has few impurities, and exhibits stable performance. [Means for solving the problem]

[0009] Therefore, the inventors conducted intensive research in view of the above problems, and unexpectedly discovered that by preparing a Li-Sn-S homogeneous solution containing at least lithium (Li), tin (Sn), and sulfur (S) in an organic solvent and using this as a raw material, a sulfide-based solid electrolyte with low impurity content can be stably produced.

[0010] That is, the present invention is as follows. <1> A dissolution step of preparing a homogeneous solution containing at least lithium (Li), tin (Sn), phosphorus (P), and sulfur (S) in an organic solvent; a drying step of removing the organic solvent from the homogeneous solution to obtain a precursor; and a heat treatment step of heat-treating the precursor to obtain a sulfide-based solid electrolyte. <2> the solution-forming step includes a solution-forming step 1 in which Li2S and P2S5 are mixed in the organic solvent to prepare a Li-PS homogeneous solution, and a solution-forming step 2 in which a Li-Sn-S homogeneous solution containing at least lithium (Li), tin (Sn), and sulfur (S) elements is prepared in the organic solvent; The Li-PS homogeneous solution and the Li-Sn-S homogeneous solution are mixed to prepare a homogeneous solution. <1> This is a method for producing the sulfide-based solid electrolyte described in the above. <3> the solution-forming step includes a solution-forming step 1 of preparing a Li-PS homogeneous solution by mixing Li2S and P2S5 in the organic solvent, a solution-forming step 2 of preparing a Li-Sn-S homogeneous solution containing at least lithium (Li), tin (Sn), and sulfur (S) in the organic solvent, and a solution-forming step 3 of preparing a Li-S homogeneous solution by mixing Li2S and S in the organic solvent; The Li-PS homogeneous solution, the Li-Sn-S homogeneous solution, and the Li-S homogeneous solution are mixed to prepare a homogeneous solution. <1> This is a method for producing the sulfide-based solid electrolyte described in the above. <4> the solution-forming step includes a solution-forming step 1 of mixing Li2S and P2S5 in the organic solvent to prepare a Li-PS homogeneous solution, a solution-forming step 2 of preparing a Li-Sn-S homogeneous solution containing at least lithium (Li), tin (Sn), and sulfur (S) in the organic solvent, a solution-forming step 3 of mixing Li2S and S in the organic solvent to prepare a Li-S homogeneous solution, and a solution-forming step 4 of preparing a Li-Si-S homogeneous solution containing at least lithium (Li), silicon (Si), and sulfur (S) in the organic solvent, The Li-PS homogeneous solution, the Li-Sn-S homogeneous solution, the Li-S homogeneous solution, and the Li-Si-S homogeneous solution are mixed to prepare a homogeneous solution. <1> This is a method for producing the sulfide-based solid electrolyte described in the above. <5> The method according to claim 1, wherein the second solution-forming step includes mixing Li2S, SnS, and S in the organic solvent to prepare a Li-Sn-S homogeneous solution. <2> from <4> 10. The method for producing the sulfide-based solid electrolyte according to claim 9, <6> The method according to claim 1, wherein the solution forming step 4 includes mixing Li2S, SiS2, and S in the organic solvent to prepare a Li-Si-S homogeneous solution. <4> This is a method for producing the sulfide-based solid electrolyte described in the above. <7> A slurrying step 1 for preparing a Li3PS4-containing slurry liquid; A solution forming step of preparing a Li-Sn-S homogeneous solution containing at least lithium (Li), tin (Sn), and sulfur (S) in an organic solvent; a slurrying step 2 of mixing the Li3PS4-containing slurry liquid and the Li-Sn-S homogeneous solution to prepare a mixed slurry liquid; a drying step of removing the organic solvent from the mixed slurry liquid to obtain a precursor; and a heat treatment step of heat-treating the precursor to obtain a sulfide-based solid electrolyte. <8> The solution forming step includes adding Li2S, SnS, and S to the organic solvent and mixing them to prepare a Li-Sn-S homogeneous solution. <7> This is a method for producing the sulfide-based solid electrolyte described in the above. <9> The organic solvent is at least one selected from the group consisting of ether solvents, nitrile solvents, and ester solvents. <1> from <8> 10. The method for producing the sulfide-based solid electrolyte according to claim 9, <10> The organic solvent is at least one selected from the group consisting of tetrahydrofuran, acetonitrile, ethyl acetate, and methyl acetate. <1> from <9> 10. The method for producing the sulfide-based solid electrolyte according to claim 9, <11> The temperature in the drying step is 60 to 280° C. <1> from <10> 10. The method for producing the sulfide-based solid electrolyte according to claim 9, <12> The temperature in the heat treatment step is 200° C. to 700° C. <1> from <11> 10. The method for producing the sulfide-based solid electrolyte according to claim 9, <13> The sulfide-based solid electrolyte contains a LGPS-based solid electrolyte and has peaks at least at 2θ=19.90°±0.50°, 20.20°±0.50°, 26.70°±0.50°, and 29.20°±0.50° in X-ray diffraction (CuKα: λ=1.5405 Å). <1> from <12> 10. The method for producing the sulfide-based solid electrolyte according to claim 9, Effect of the Invention

[0011] According to the present invention, a method for producing a sulfide-based solid electrolyte having excellent productivity, less impurities and stable performance can be provided. In particular, a sulfide-based solid electrolyte having high ionic conductivity can be produced by synthesis using a Li-Sn-S homogeneous solution, compared to the case where SnS2, which is an insoluble raw material, is used. In addition, according to the present invention, a molded body obtained by heating and molding the sulfide-based solid electrolyte, and an all-solid-state battery including the sulfide-based solid electrolyte can be provided. Moreover, this manufacturing method can be applied to mass production. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic diagram showing a crystal structure of a sulfide-based solid electrolyte according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view of an all-solid-state battery according to one embodiment of the present invention. [Diagram 3] 1 is a graph showing the results of X-ray diffraction measurement of the sulfide-based solid electrolytes obtained in Examples 1 to 4 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below. Note that the materials and configurations described below do not limit the present invention, and various modifications can be made within the scope of the present invention. The first embodiment of the present invention includes a solution forming step of preparing a homogeneous solution containing at least lithium (Li), tin (Sn), phosphorus (P), and sulfur (S) in an organic solvent; a drying step of removing the organic solvent from the homogeneous solution to obtain a precursor; and a heat treatment step of heat-treating the precursor to obtain a sulfide-based solid electrolyte. In the present invention, a homogeneous solution containing at least lithium (Li), tin (Sn), phosphorus (P), and sulfur (S) in an organic solvent is defined as a solution containing at least lithium (Li), tin (Sn), phosphorus (P), and sulfur (S) in an organic solvent and containing no undissolved precipitate.

[0014] In the first embodiment of the present invention, the solution-formation process preferably includes solution-formation process 1 in which Li2S and P2S5 are mixed in the organic solvent to prepare a Li-PS homogeneous solution, and solution-formation process 2 in which a Li-Sn-S homogeneous solution containing at least lithium (Li), tin (Sn), and sulfur (S) elements is prepared in the organic solvent, and includes mixing the Li-PS homogeneous solution and the Li-Sn-S homogeneous solution to prepare a homogeneous solution. In addition, in the first embodiment of the present invention, in addition to the above-mentioned solution-forming steps 1 and 2, it is also preferable that the solution-forming step includes solution-forming step 3 of preparing a Li-S homogeneous solution by mixing Li2S and S in the organic solvent, and that the Li-PS homogeneous solution, the Li-Sn-S homogeneous solution, and the Li-S homogeneous solution are mixed to prepare a homogeneous solution. Furthermore, in the first embodiment of the present invention, in addition to the above-mentioned solution forming steps 1 to 3, it is also preferable that the solution forming step includes solution forming step 4 of preparing a Li-Si-S homogeneous solution containing at least lithium (Li), silicon (Si), and sulfur (S) in the organic solvent, and that the Li-PS homogeneous solution, the Li-Sn-S homogeneous solution, the Li-S homogeneous solution, and the Li-Si-S homogeneous solution are mixed to prepare a homogeneous solution.

[0015] The solution forming steps 1 to 4, the drying step, and the heat treatment step will be described in detail below. In the present invention, the term "Li-PS homogeneous solution" is defined as a solution containing at least lithium (Li), phosphorus (P), and sulfur (S) in an organic solvent, and free of undissolved precipitates. Similarly, the term "Li-Sn-S homogeneous solution" is defined as a solution containing at least lithium (Li), tin (Sn), and sulfur (S) in an organic solvent, and free of undissolved precipitates. Furthermore, the term "Li-S homogeneous solution" is defined as a solution containing at least lithium (Li), and sulfur (S) in an organic solvent, and free of undissolved precipitates. Furthermore, the term "Li-Si-S homogeneous solution" is defined as a solution containing at least lithium (Li), silicon (Si), and sulfur (S) in an organic solvent, and free of undissolved precipitates.

[0016] <Solution process 1> The solution forming step 1 is a step of preparing a Li-PS homogeneous solution by mixing Li2S and P2S5 in an organic solvent. Preferably, the Li-PS homogeneous solution is prepared by mixing Li2S and P2S5 in an organic solvent so that the molar ratio of Li2S / P2S5 is 0.7 to 1.5. During mixing in the solution-making step 1, the substrate is in a dispersed slurry state, but it will eventually react. No special stirring operation to crush the particles is required; it is sufficient to apply a stirring force sufficient to suspend and disperse the slurry. The reaction temperature in the solution-forming step 1 is such that the reaction proceeds slowly even at room temperature, but it can also be heated to increase the reaction rate. When heating, it is sufficient to carry out the reaction at a temperature below the boiling point of the organic solvent, which is usually less than 120°C, although this varies depending on the organic solvent used. It is also possible to carry out the reaction under pressure using an autoclave or the like, but there is a concern that side reactions may proceed if the mixture is mixed at a high temperature of 120°C or higher.

[0017] The reaction time in the solution-forming step 1 varies depending on the type of organic solvent and the particle size and concentration of the raw material, but the reaction is completed and the solution can be formed by performing the reaction for, for example, 0.1 to 24 hours.

[0018] The Li-PS homogeneous solution is preferably produced by mixing and reacting Li2S and P2S5 in an organic solvent so that the molar ratio of Li2S / P2S5 is 0.7 to 1.5, more preferably Li2S / P2S5=0.75 to 1.4, and particularly preferably Li2S / P2S5=0.8 to 1.35. When the molar ratio of Li2S / P2S5 is in the range of 0.7 to 1.5, Li2S and P2S5 can be put into solution at room temperature. If the molar ratio is outside the above range, precipitation may occur. This solution may contain unreacted Li2S or P2S5. It may also contain impurities that have been mixed in from Li2S or P2S5. Since the impurities are hardly dissolved in the solvent and most of them precipitate, it is preferable to obtain a homogeneous solution of high purity Li-PS by filtering or centrifuging the obtained solution to remove the precipitate and separate the solution.

[0019] Li2S can be used either synthetically or commercially available. Since the inclusion of moisture deteriorates other raw materials and precursors, the moisture content is preferably low, more preferably 300 ppm or less, and particularly preferably 50 ppm or less. The particle size of Li2S is preferably small because the reaction rate is faster. The particle diameter is preferably in the range of 10 nm to 100 μm, more preferably 100 nm to 30 μm, and particularly preferably 300 nm to 10 μm. The particle size can be measured by SEM or a particle size distribution measuring device using laser scattering. The Li2S used in the solution formation steps 2 to 4 described later can also be preferably the same as above.

[0020] P2S5 may be either a synthetic product or a commercially available product. A higher purity of P2S5 is preferable because fewer impurities are mixed into the solid electrolyte. A smaller particle size of P2S5 is preferable because the reaction rate is faster. The particle diameter is preferably in the range of 10 nm to 100 μm, more preferably 100 nm to 30 μm, and particularly preferably 300 nm to 10 μm. The moisture content is preferably low because it deteriorates other raw materials and precursors, more preferably 300 ppm or less, and particularly preferably 50 ppm or less.

[0021] The organic solvent is not particularly limited as long as it is an organic solvent that does not react with Li2S and P2S5. For example, ether solvents, ester solvents, hydrocarbon solvents, nitrile solvents, etc. can be mentioned. Specifically, tetrahydrofuran, cyclopentyl methyl ether, diisopropyl ether, diethyl ether, dimethyl ether, dioxane, methyl acetate, ethyl acetate, butyl acetate, acetonitrile, etc. can be mentioned. Among these, at least one selected from the group consisting of tetrahydrofuran, acetonitrile, ethyl acetate, and methyl acetate is preferable, and acetonitrile is particularly preferable. Since acetonitrile does not contain oxygen atoms in its structure, oxygen is unlikely to be introduced into the raw material composition, and deterioration is suppressed. In addition, in order to prevent deterioration of the raw material composition, it is preferable to remove oxygen and water from the organic solvent, and in particular, the moisture content is preferably 100 ppm or less, more preferably 50 ppm or less. The organic solvent used in the solution formation steps 2 to 4 described later can also be preferably the same as above.

[0022] <Solution process 2> The solution forming step 2 is a step of preparing a Li-Sn-S homogeneous solution containing at least lithium (Li), tin (Sn), and sulfur (S) in an organic solvent. Preferably, the solution forming step 2 prepares the Li-Sn-S homogeneous solution by mixing Li2S, SnS, and S (elemental sulfur) in an organic solvent. Conventional sulfide-based solid electrolytes containing Sn often use SnS2, a sulfide of Sn, as a raw material. However, SnS2 has poor solubility in solvents. Therefore, in the synthesis in a solvent, it is difficult to uniformly disperse Sn in the solid electrolyte during synthesis, and there is a problem that it is difficult to obtain a solid electrolyte that exhibits stable performance. The present inventors have found that by using a combination of Li2S, SnS, and S, it is possible to prepare a Li-Sn-S uniform solution in which these are dissolved in an organic solvent.

[0023] In the solution formation step 2, more preferably, Li2S, SnS, and S are mixed in an organic solvent so that the molar ratio of Li2S:SnS:S is 2:1:12 to 6:1:36, and particularly preferably, Li2S, SnS, and S are mixed in an organic solvent so that the molar ratio of Li2S:SnS:S is 3:1:18 to 5:1:30, to prepare a Li-Sn-S homogeneous solution. During mixing in the solution-making step 2, the substrate is in a dispersed slurry state, but will eventually react. No special stirring operation to crush particles is required; it is sufficient to apply a stirring force sufficient to suspend and disperse the slurry. The reaction temperature in the solution-forming step 2 is sufficient if it is performed at or below the boiling point of the organic solvent, and although it varies depending on the organic solvent used, it is usually less than 120° C. The reaction temperature is preferably 50 to 100° C., more preferably 60 to 90° C. Although it is possible to perform the reaction under pressure using an autoclave or the like, there is a concern that side reactions may proceed if mixing is performed at a high temperature of 120° C. or higher.

[0024] The reaction time in the solution-forming step 2 varies depending on the type of organic solvent and the particle size and concentration of the raw material, but the reaction is completed and the solution can be formed by performing the reaction for, for example, 0.1 to 24 hours. This solution may contain unreacted Li2S, SnS, or S. It may also contain impurities mixed in from Li2S, SnS, or S. Since the impurities are hardly dissolved in the solvent and most of them precipitate, it is preferable to obtain a homogeneous solution of high purity Li-Sn-S by filtering or centrifuging the obtained solution to remove the precipitate and separate the solution. The concentration of each element in the obtained homogeneous solution is analyzed by ICP, and the molar ratio of Li:Sn:S is preferably 4:1:15 to 12:1:43, more preferably Li:Sn:S = 5:1:18 to 11:1:40, and particularly preferably Li:Sn:S = 6:1:22 to 10:1:36.

[0025] SnS can be used either synthetically or commercially available. Higher purity of SnS is preferable because fewer impurities are mixed into the solid electrolyte. Smaller particle size of SnS is preferable because the reaction rate is faster. The particle diameter is preferably in the range of 10 nm to 100 μm, more preferably 100 nm to 30 μm, and particularly preferably 300 nm to 10 μm. The particle size can be measured by SEM or a particle size distribution measuring device using laser scattering. Note that even if some of the above raw materials are amorphous, they can be used without any problems. The inclusion of moisture deteriorates other raw materials and precursors, so it is preferable that the moisture content is low, more preferably 300 ppm or less, and particularly preferably 50 ppm or less.

[0026] Although the elemental sulfur may be a synthetic product or a commercially available product, cyclic S8 sulfur is generally used. Since the inclusion of moisture deteriorates other raw materials and precursors, the moisture content is preferably low, more preferably 300 ppm or less, and particularly preferably 50 ppm or less. The particle size of the elemental sulfur is preferably small because the reaction rate is faster. The particle diameter is preferably in the range of 10 nm to 100 μm, more preferably 100 nm to 30 μm, and particularly preferably 300 nm to 10 μm. The S (elemental sulfur) used in the solution formation steps 3 and 4 described later can also be preferably the same as above.

[0027] <Solution process 3> The solution forming step 3 is a step of preparing a homogeneous Li-S solution by mixing Li2S and S (elemental sulfur) in an organic solvent. In the solution formation step 3, Li2S and S are mixed in an organic solvent, preferably so that the molar ratio of Li2S:S is 1:4 to 1:10, more preferably so that the molar ratio of Li2S:S is 1:5 to 1:8, to prepare a Li-S homogeneous solution. During mixing in the solution-forming step 3, the substrate is in a dispersed slurry state, but will eventually react. No special stirring operation to crush particles is required; it is sufficient to apply a stirring force sufficient to suspend and disperse the slurry. The reaction temperature in the solution-forming step 3 is sufficient if it is performed at or below the boiling point of the organic solvent, and although it varies depending on the organic solvent used, it is usually less than 120° C. The reaction temperature is preferably 50 to 100° C., more preferably 60 to 90° C. Although it is possible to perform the reaction under pressure using an autoclave or the like, there is a concern that side reactions may proceed if mixing is performed at a high temperature of 120° C. or higher.

[0028] The reaction time in the solution-forming step 3 varies depending on the type of organic solvent and the particle size and concentration of the raw material, but the reaction is completed and the solution can be formed by performing the reaction for, for example, 0.1 to 24 hours. This solution may contain unreacted Li2S and S. It may also contain impurities mixed in from Li2S and S. Since the impurities are hardly dissolved in the solvent and most of them precipitate, it is preferable to obtain a homogeneous solution of high purity Li-S by filtering or centrifuging the obtained solution to remove the precipitate and separate the solution.

[0029] <Solution process 4> The solution forming step 4 is a step of preparing a Li-Si-S homogeneous solution containing at least lithium (Li), silicon (Si), and sulfur (S) in an organic solvent. By using the Li-Si-S homogeneous solution, a sulfide-based solid electrolyte having a small amount of impurities and high ionic conductivity can be stably obtained. When SiS2 is used as a starting material, it is difficult to uniformly disperse Si in the solid electrolyte during synthesis. In addition, SiS2 is highly reactive with the air and often contains oxygen-containing compounds or unreacted Si as a raw material, making it difficult to prepare SiS2 that does not contain impurities. In addition, it is difficult to remove these impurities from SiS2. On the other hand, in the case of a Li-Si-S homogeneous solution, Si is easily dispersed uniformly in the solid electrolyte during synthesis, and impurities are reduced through the subsequent precipitation removal process, making it less likely that side reactions will occur. This is thought to enable the production of a sulfide-based solid electrolyte with stable high ionic conductivity.

[0030] The Li-Si-S homogeneous solution is preferably prepared by mixing and reacting Li2S, SiS2, and S (elemental sulfur) in an organic solvent to obtain a solution in which Li, Si, and S are dissolved. This solution may contain unreacted Li2S, SiS2, and S. It may also contain impurities that are mixed in from Li2S, SiS2, and S. More preferably, the resulting solution is filtered or centrifuged to remove precipitates and separate the solution, thereby obtaining a homogeneous solution of Li-Si-S. The concentration of each element in the resulting homogeneous solution is analyzed by ICP, and the molar ratio of Li / Si is preferably 0.6 to 2.0. Here, the molar ratio is more preferably Li / Si=0.7 to 1.6, and particularly preferably Li / Si=0.8 to 1.4.

[0031] The precipitate can be removed by filtration or centrifugation. When filtration is performed using a filter, the pore size of the filter is desirably 10 μm or less, more desirably 5 μm or less, and particularly desirably 2 μm or less.

[0032] The precipitates are unreacted raw materials such as Li2S and SiS2, as well as impurities mixed in from SiS2. Impurities include oxygen-containing compounds of Si and SiS2, and SiO2.

[0033] SiS2 can be used either synthetically or commercially available. The higher the purity of SiS2, the fewer the impurities that are mixed into the solid electrolyte. The smaller the particle size of SiS2, the faster the reaction rate, so it is preferable. The particle diameter is preferably in the range of 10 nm to 100 μm, more preferably 100 nm to 30 μm, and particularly preferably 300 nm to 10 μm. The particle size can be measured by SEM or a particle size distribution measuring device using laser scattering. Note that even if some of the above raw materials are amorphous, they can be used without any problems. The moisture content is preferably low, more preferably 300 ppm or less, and particularly preferably 50 ppm or less, since it deteriorates other raw materials and precursors.

[0034] The total concentration of Li, Si and S in the organic solvent is preferably 0.5 to 20 mass%, more preferably 1 to 15 mass%, and particularly preferably 2 to 10 mass%. If the total concentration of Li, Si and S in the organic solvent is higher than 20 mass%, it becomes difficult to obtain a homogeneous solution due to solid precipitation. On the other hand, if the total concentration of Li, Si and S in the organic solvent is lower than 0.5 mass%, a large amount of organic solvent will be used, which increases the burden of solvent recovery and causes the size of the reactor to become excessively large.

[0035] <Preparation of homogeneous mixed solution> In the first embodiment of the present invention, it is preferable to prepare a homogeneous mixed solution by (i) mixing the Li-PS homogeneous solution obtained in solution-making process 1 with the Li-Sn-S homogeneous solution obtained in solution-making process 2, or (ii) mixing the Li-PS homogeneous solution obtained in solution-making process 1 with the Li-Sn-S homogeneous solution obtained in solution-making process 2 and the Li-S homogeneous solution obtained in solution-making process 3, or (iii) mixing the Li-PS homogeneous solution obtained in solution-making process 1 with the Li-Sn-S homogeneous solution obtained in solution-making process 2 with the Li-S homogeneous solution obtained in solution-making process 3 and the Li-Si-S homogeneous solution obtained in solution-making process 4. The concentrations of the elements constituting the homogeneous mixed solution obtained in the above (i) are preferably in a molar ratio of Li:Sn:P=8:1:1 to 15:1:4, and more preferably Li:Sn:P=10:1:2 to 13:1:3. The concentrations of the elements constituting the homogeneous mixed solution obtained in (ii) above are preferably in a molar ratio of Li:Sn:P=8:1:1 to 15:1:4, more preferably Li:Sn:P=10:1:2 to 13:1:3. Furthermore, the concentrations of the elements constituting the homogeneous mixed solution obtained in (iii) above are preferably in a molar ratio of Li:Sn:Si:P=32:1:2:4 to 44:1:6:8, and more preferably Li:Sn:Si:P=35:1:3:5 to 41:1:5:7.

[0036] The type and concentration of elements can be confirmed, for example, by an ICP emission spectrometer. Since the performance of the sulfide-based solid electrolyte changes significantly due to a slight deviation in the composition, it is preferable to precisely control the element composition by performing ICP emission spectrometer on a homogeneous solution. A halogen compound can also be added here. In this case, it is preferable that the halogen compound is also dissolved in the organic solvent. Specific examples of the halogen compound include LiCl, LiBr, LiI, PCl5, PCl3, PBr5 and PBr3, and more preferably LiCl, LiBr and LiI. These may be used alone or in combination of two or more.

[0037] <Drying process> The drying step is a step of obtaining a precursor by drying the obtained homogeneous solution to remove the organic solvent, and is preferably performed by heating and drying in an inert gas atmosphere or vacuum drying. The drying temperature is preferably in the range of 60 to 280°C, more preferably 100 to 250°C. The optimum range varies somewhat depending on the type of organic solvent, but the temperature range is important. If the drying temperature is too high in the presence of an organic solvent, the precursor will be altered in most cases. If the drying temperature is too low, the amount of residual solvent will increase, and if the next heat treatment step is performed as is, the organic solvent will be carbonized, and the electronic conductivity of the resulting sulfide-based solid electrolyte will be high. Depending on the method of using the solid electrolyte, it is preferable for it to have electronic conductivity, but the solid electrolyte used in the second part of Figure 2 is required to have sufficiently low electronic conductivity. When using it for such purposes, it is necessary to minimize the amount of residual solvent.

[0038] The drying time varies depending on the type of organic solvent and the drying temperature, but the organic solvent can be sufficiently removed by performing the drying for 1 to 24 hours. The temperature for removing the organic solvent can be lowered and the required time can be shortened by removing the organic solvent under reduced pressure, such as by vacuum drying, or by flowing an inert gas such as nitrogen or argon that has a sufficiently low moisture content. It is also possible to carry out the subsequent heating process and drying process simultaneously.

[0039] <Heat treatment process> The heat treatment step is a step of heat treating the precursor obtained in the drying step to obtain a sulfide-based solid electrolyte. The heating temperature is usually preferably in the range of 200 to 700° C., more preferably in the range of 350 to 650° C., and particularly preferably in the range of 400 to 600° C. If the temperature is lower than the above range, the desired crystals are unlikely to form, whereas if the temperature is higher than the above range, crystals other than the intended one may form.

[0040] Although the heating time varies slightly depending on the heating temperature, a heating time in the range of 0.1 to 24 hours is usually sufficient for crystallization. Heating at a high temperature for a long period of time exceeding the above range is not preferable because there is a concern that the sulfide-based solid electrolyte may be altered. Heating can be performed in a vacuum or in an inert gas atmosphere, but is preferably performed in an inert gas atmosphere. As the inert gas, nitrogen, helium, argon, etc. can be used, among which argon is preferred. It is preferable that the oxygen and moisture content are low, and the conditions are the same as those during mixing in the slurrying step.

[0041] The second embodiment of the present invention includes a slurrying step 1 for preparing a Li3PS4-containing slurry liquid; A solution forming step of preparing a Li-Sn-S homogeneous solution containing at least lithium (Li), tin (Sn), and sulfur (S) in an organic solvent; a slurrying step 2 of mixing the Li3PS4-containing slurry liquid and the Li-Sn-S homogeneous solution to prepare a mixed slurry liquid; a drying step of removing the organic solvent from the mixed slurry liquid to obtain a precursor; and a heat treatment step of heat-treating the precursor to obtain a sulfide-based solid electrolyte. The slurry formation step 1 in the second embodiment is not particularly limited as long as it is capable of preparing a Li3PS4-containing slurry liquid, but it is preferable to prepare a Li3PS4-containing slurry liquid by mixing Li2S and P2S5 in an organic solvent so that the molar ratio of Li2S / P2S5 is 2 to 4. The other steps in the second embodiment can be performed in accordance with the steps described in the first embodiment.

[0042] The LGPS type crystal structure is composed of an octahedron O composed of Li and S elements, a tetrahedron T1 composed of one or more elements selected from the group consisting of P, Ge, Si, and Sn and S elements, and a tetrahedron T2 composed of P and S elements (PS4 3- Anion) in which the tetrahedron T1 and the octahedron O share edges, and the tetrahedron T2 and the octahedron O share vertices. Solid electrolytes with LGPS-type crystal structures are more preferable because they have particularly high ionic conductivity. LGPS-based solid electrolytes containing Si tend to generate hydrogen sulfide when they come into contact with water, but Sn does not generate hydrogen sulfide even when it comes into contact with water, and has the advantages of being highly safe and easy to manufacture.

[0043] The solid electrolyte having an LGPS type crystal structure, which is a preferred embodiment of the present invention, preferably has peaks at least at 2θ=19.90°±0.50°, 20.20°±0.50°, 26.70°±0.50°, and 29.20°±0.50° in X-ray diffraction measurement (CuKα: λ=1.5405 Å).

[0044] The sulfide-based solid electrolyte of the present invention obtained as described above can be formed into a desired molded body by various means and used in various applications including the all-solid-state battery described below. The molding method is not particularly limited. For example, the same molding method as the molding method for each layer constituting the all-solid-state battery described in <All-solid-state battery> described later can be used.

[0045] <All-solid-state battery> The sulfide-based solid electrolyte of the present invention can be used, for example, as a solid electrolyte for an all-solid-state battery. According to a further embodiment of the present invention, there is provided an all-solid-state battery including the above-mentioned solid electrolyte for an all-solid-state battery.

[0046] Here, the "all-solid-state battery" refers to an all-solid-state lithium-ion secondary battery. FIG. 2 is a schematic cross-sectional view of an all-solid-state battery according to one embodiment of the present invention. The all-solid-state battery 10 has a structure in which a solid electrolyte layer 2 is disposed between a positive electrode layer 1 and a negative electrode layer 3. The all-solid-state battery 10 can be used in various devices including mobile phones, personal computers, and automobiles. The sulfide-based solid electrolyte of the present invention may be contained as a solid electrolyte in at least one of the positive electrode layer 1, the negative electrode layer 3, and the solid electrolyte layer 2. When the sulfide-based solid electrolyte of the present invention is contained in the positive electrode layer 1 or the negative electrode layer 3, the sulfide-based solid electrolyte of the present invention is used in combination with a known positive electrode active material or negative electrode active material for lithium ion secondary batteries. The amount ratio of the sulfide-based solid electrolyte of the present invention contained in the positive electrode layer 1 or the negative electrode layer 3 is not particularly limited. The sulfide-based solid electrolyte of the present invention may be composed of a single material, or may be composed of an oxide solid electrolyte (e.g., Li7La3Zr2O 12 ), sulfide-based solid electrolytes (e.g., Li2S-P2S5), and other complex hydride solid electrolytes (e.g., LiBH4, 3LiBH4-LiI), etc., may be used in appropriate combination.

[0047] The all-solid-state battery is produced by forming and laminating each of the layers described above, but there are no particular limitations on the method for forming and laminating each layer. For example, there are a method in which a solid electrolyte and / or an electrode active material is dispersed in a solvent to form a slurry, which is then applied by a doctor blade or spin coating, and then rolled to form a film; a gas phase method in which a film is formed and laminated using a vacuum deposition method, an ion plating method, a sputtering method, a laser ablation method, or the like; and a pressure molding method in which a powder is molded by a hot press or a cold press without applying heat, and then the formed film is laminated.

[0048] Since the sulfide-based solid electrolyte of the present invention is relatively soft, it is particularly preferable to form and stack each layer by pressure molding to produce an all-solid-state battery. Pressure molding methods include hot pressing, which is performed with heating, and cold pressing, which is not performed with heating, but cold pressing can also be used to sufficiently form the electrolyte. The present invention includes a molded body obtained by hot molding the sulfide-based solid electrolyte of the present invention. The molded body is suitably used as an all-solid-state battery. The present invention also includes a method for producing an all-solid-state battery, which includes a step of hot molding the sulfide-based solid electrolyte of the present invention. EXAMPLES

[0049] The present embodiment will be described in more detail below with reference to examples, but the present embodiment is not limited to these examples.

[0050] Example 1 <Solution process 1> In a glove box under an argon atmosphere, 101 mg of Li2S (Sigma-Aldrich, purity 99.8%) and 487 mg of P2S5 (Sigma-Aldrich, purity 99%) were weighed out so that the molar ratio of Li2S:P2S5:=1:1. Next, Li2S and P2S5 were added in that order to 6.0 g of acetonitrile (Wako Pure Chemical Industries, ultra-dehydrated grade) so that the concentration of (Li2S + P2S5) was approximately 10 mass%, and mixed at room temperature for 3 hours. The mixture gradually dissolved, and a Li-PS homogeneous solution was obtained.

[0051] <Solution process 2> In a glove box under an argon atmosphere, 1.0 g of Li2S (Sigma-Aldrich, purity 99.8%), 1.0 g of SnS (Kojundo Chemical Co., Ltd.), and 3.7 g of S (Kojundo Chemical Co., Ltd.) were weighed out so that the molar ratio of Li2S:SnS:S was 3:1:18. Next, 100 g of acetonitrile (Wako Pure Chemical Industries, ultra-dehydrated grade) was added so that the concentration of (Li2S+SnS+S) was approximately 6 mass%, and the mixture was mixed at 80°C for 24 hours. The mixture gradually dissolved, but insoluble matter remained at this stage. The resulting solution was filtered using a membrane filter (PTFE, pore size 1.0 μm) to obtain 300 mg of filtrate and 100 g of filtrate (Li-Sn-S homogeneous solution). ICP analysis of the Li-Sn-S homogeneous solution showed that the molar ratio was Li:Sn:S=6:1:26. The Sn concentration was 0.76 mass%.

[0052] <Solution process 3> In a glove box under an argon atmosphere, 1.0 g of Li2S (Sigma-Aldrich, purity 99.8%) and 3.7 g of S (Kojundo Chemical) were weighed out so that the molar ratio of Li2S:S was 1:6. Next, 75 g of acetonitrile (Wako Pure Chemical Industries, ultra-dehydrated grade) was added so that the concentration of (Li2S+S) was approximately 6 mass%, and the mixture was mixed at 80°C for 24 hours. The mixture gradually dissolved, but insoluble matter remained at this stage. The resulting solution was filtered using a membrane filter (PTFE, pore size 1.0 μm) to obtain 200 mg of filtrate and 75 g of filtrate (Li-S homogeneous solution). ICP analysis of the Li-S homogeneous solution showed that the molar ratio was Li:S=1:3. The Li concentration was 0.5% by mass.

[0053] <Preparation of homogeneous mixed solution> The Li-PS homogeneous solution (6.6 g), the Li-Sn-S homogeneous solution (25.08 g), and the Li-S homogeneous solution (7.97 g) prepared above were mixed so as to obtain a molar ratio of Li:Sn:P=12:1:3, and the mixture was stirred for 3 hours to prepare a homogeneous mixed solution.

[0054] <Drying process> The resulting homogeneous mixed solution was dried under vacuum at 180°C for 4 hours to remove the solvent. The solvent was removed while stirring the solution. The solution was then cooled to room temperature to obtain a precursor.

[0055] <Heat treatment process> The obtained precursor was placed in a glass reaction tube in a glove box and placed in an electric tube furnace to prevent the precursor from being exposed to the atmosphere. Argon (G3 grade) was blown into the reaction tube, and the temperature was raised to 550 °C over 3 hours, and then calcined at 550 °C for 8 hours to obtain Li 9.81 Sn 0.81 P 2.19 S 12 Crystals were synthesized.

[0056] Example 2 <Solution process 1> The same procedure as in Example 1 was carried out to obtain a Li-PS homogeneous solution. <Solution process 2> In a glove box under an argon atmosphere, 1.25 g of Li2S (Sigma-Aldrich, purity 99.8%), 1 g of SnS (Kojundo Chemical Co., Ltd.), and 5 g of S (Kojundo Chemical Co., Ltd.) were weighed out so that the molar ratio of Li2S:SnS:S was 4.5:1:24. Next, 100 g of acetonitrile (Wako Pure Chemical Industries, ultra-dehydrated grade) was added so that the concentration of (Li2S+SnS+S) was approximately 7% by mass, and the mixture was mixed at 80°C for 24 hours. The mixture gradually dissolved, but insoluble matter remained at this stage. The resulting solution was filtered using a membrane filter (PTFE, pore size 1.0 μm) to obtain 300 mg of filtrate and 100 g of filtrate (Li-Sn-S homogeneous solution). ICP analysis of the Li-Sn-S homogeneous solution showed that the molar ratio was Li:Sn:S=9:1:30. The Sn concentration was 0.89 mass%. <Preparation of homogeneous mixed solution> 6.6 g of the Li-PS uniform solution and 33.28 g of the Li-Sn-S uniform solution prepared above were mixed so as to have a molar ratio of Li:Sn:P=12:1:3, and the mixture was stirred for 3 hours to prepare a uniform mixed solution.

[0057] <Drying process> The same procedure as in Example 1 was carried out to obtain a precursor. <Heat treatment process> The same procedure as in Example 1 was carried out to obtain Li 9.81 Sn 0.81 P2.19 S 12 Crystals were synthesized.

[0058] Comparative Example 1 <Solution process> The same procedure as in Example 1 was carried out to obtain a Li-PS homogeneous solution. <Slurrying process> A slurry solution was prepared by mixing 6.6 g of the Li-PS homogeneous solution prepared above, 296 mg of powdered SnS2 (manufactured by Kojundo Chemical Co., Ltd.), and 350 mg of Li2S to obtain a molar ratio of Li:Sn:P = 12:1:3, and stirring for 3 hours. Here, Sn was not completely dissolved in the organic solvent. <Drying process> The obtained slurry solution was dried under vacuum at 180°C for 4 hours to remove the solvent. The solvent was removed while stirring the solution. The solution was then cooled to room temperature to obtain a precursor. <Heat treatment process> The same procedure as in Example 1 was carried out to obtain Li 9.81 Sn 0.81 P 2.19 S 12 Crystals were synthesized.

[0059] Example 3 <Solution process 1> The same procedure as in Example 1 was carried out to obtain a Li-PS homogeneous solution. <Solution process 2> The same procedure as in Example 1 was carried out to obtain a Li-Sn-S homogeneous solution. <Solution process 3> The same procedure as in Example 1 was carried out to obtain a Li-S homogeneous solution. <Solution process 4> In a glove box under an argon atmosphere, 4.0 g of Li2S (Sigma-Aldrich, purity 99.8%), 16.0 g of SiS2 (HANGZHOU), and 2.4 g of S (Kojundo Kagaku) ​​were weighed out so that the molar ratio of Li2S:SiS2:S was 0.5:1:0.4. Next, 610 g of acetonitrile (Wako Pure Chemical Industries, ultra-dehydrated grade) was added so that the concentration of (Li2S+SiS2+S) was approximately 3.5% by mass, and the mixture was mixed at room temperature for 24 hours. The mixture gradually dissolved, but impurities in the raw materials remained at this stage. The resulting solution was filtered using a membrane filter (PTFE, pore size 1.0 μm) to obtain 2.0 g of filtrate and 578 g of filtrate (Li-Si-S homogeneous solution). ICP analysis of the Li-Si-S homogeneous solution showed that the Li:Si:S (molar ratio) was 1:1:3. The concentration of (Li2S+SiS2+S) was 3.43 mass%.

[0060] <Preparation of homogeneous mixed solution> To obtain a molar ratio of Li:Sn:Si:P=38:1:4:6, 6.6 g of the Li-PS uniform solution, 11.11 g of the Li-Sn-S uniform solution, 13.48 g of the Li-Si-S uniform solution, and 22.93 g of the Li-S uniform solution were mixed and stirred for 3 hours to prepare a uniform mixed solution.

[0061] <Drying process> The resulting homogeneous mixed solution was dried under vacuum at 180°C for 4 hours to remove the solvent. The solvent was removed while stirring the solution. The solution was then cooled to room temperature to obtain a precursor. <Heat treatment process> The obtained precursor was placed in a glass reaction tube in a glove box and placed in an electric tube furnace to prevent the precursor from being exposed to the atmosphere. Argon (G3 grade) was blown into the reaction tube, and the temperature was raised to 550 °C over 3 hours, and then calcined at 550 °C for 8 hours to obtain Li 10.35 Sn 0.27 S 1.08 P 1.65 S 12 Crystals were synthesized.

[0062] Comparative Example 2 <Solution process 1> The same procedure as in Example 1 was carried out to obtain a Li-PS homogeneous solution. <Solution process 2> The same procedure as in Example 3 was carried out to obtain a Li-Si-S homogeneous solution. <Slurry mixing process> A slurry solution was prepared by mixing 6.6 g of the Li-PS homogeneous solution prepared above, 131 mg of powdered SnS2, 13.48 g of the Li-Si-S homogeneous solution, and 461 mg of Li2S to obtain a molar ratio of Li:Sn:Si:P = 38:1:4:6, and stirring for 3 hours. Here, Sn was not completely dissolved in the organic solvent.

[0063] <Drying process> The obtained slurry solution was dried under vacuum at 180°C for 4 hours to remove the solvent. The solvent was removed while stirring the solution. The solution was then cooled to room temperature to obtain a precursor. <Heat treatment process> The same procedure as in Example 3 was carried out to obtain Li 10.35 Sn 0.27 S 1.08 P 1.65 S 12 Crystals were synthesized.

[0064] Example 4 <Slurrying process 1> In a glove box under an argon atmosphere, 236 mg of Li2S (Sigma-Aldrich, purity 99.8%) and 487 mg of P2S5 (Sigma-Aldrich, purity 99%) were weighed out so that the molar ratio of Li2S:P2S5: was 2.4:1. Next, Li2S and P2S5 were added in that order to 7.0 g of acetonitrile (Wako Pure Chemical Industries, ultra-dehydrated grade) so that the concentration of (Li2S + P2S5) was approximately 10 mass%, and mixed at room temperature for 12 hours. A precipitation of Li3PS4 occurred, and a slurry containing Li3PS4 was obtained.

[0065] <Solution process> The same operations as in Example 1 were performed to obtain a Li-Sn-S homogeneous solution. <Slurrying Step 2> 7.72 g of the Li3PS4-containing slurry solution prepared above and 20.71 g of the Li-Sn-S homogeneous solution were mixed so that the molar ratio of Li:Sn:P was 12:1:3, and the mixture was stirred for 3 hours to prepare a slurry mixed solution.

[0066] <Drying Step> The obtained slurry mixed solution was dried at 180 °C for 4 hours under vacuum to remove the solvent. The solvent removal was carried out while stirring the solution. Then, it was cooled to room temperature to obtain a precursor. <Heat Treatment Step> The same operations as in Example 1 were performed to synthesize Li 9.81 Sn 0.81 P 2.19 S 12 crystals.

[0067] <X-ray Diffraction Measurement> Regarding the powders of the sulfide-based solid electrolytes obtained in Examples 1 to 4 and Comparative Examples 1 to 2, X-ray diffraction measurements (PANalytical's "X'Pert3 Powder", CuKα: λ = 1.5405 Å) were carried out at room temperature (25 °C) under an Ar atmosphere. The results of the X-ray diffraction measurements of the sulfide-based solid electrolytes obtained in Examples 1 to 4 and Comparative Examples 1 to 2 are shown in Figure 3. As shown in Figure 3, in Examples 1 to 4 and Comparative Examples 1 to 2, diffraction peaks were observed at least at 2θ = 19.90° ± 0.50°, 20.20° ± 0.50°, 26.70° ± 0.50°, and 29.20° ± 0.50°. This pattern is consistent with that of Li 10 GeP2S 12 in the ICSD database, and it was confirmed that it has an LGPS-type crystal structure. Also, many impurity peaks were confirmed in Comparative Example 1. These are considered to be impurities confirmed because SnS2 in the raw materials had poor solubility in the solvent, and thus Sn was not uniformly dispersed in the solid electrolyte during synthesis.

[0068] <Lithium Ion Conductivity Measurement> The sulfide-based solid electrolytes obtained in Examples 1 to 4 and Comparative Examples 1 and 2 were subjected to uniaxial molding (420 MPa) to obtain disks with a thickness of about 1 mm and a diameter of 10 mm. Using an all-solid-state battery evaluation cell (manufactured by Hosen Co., Ltd.), AC impedance measurements were performed by the four-terminal method (Solartron's "SI1260 IMPEDANCE / GAIN-PHASE ANALYZER") at room temperature (25°C) to calculate the lithium ion conductivity. Specifically, the sample was placed in a thermostatic chamber set at 25°C and held for 30 minutes, after which the lithium ion conductivity was measured. The measurement frequency range was 0.1Hz to 1MHz, and the amplitude was 50mV. The measurement results of the lithium ion conductivity are shown in Table 1 below.

[0069] [Table 1] [Explanation of symbols]

[0070] 1 Positive electrode layer 2 Solid electrolyte layer 3. Negative electrode layer 10 All-solid-state battery

Claims

1. A solution forming step of preparing a homogeneous solution containing at least lithium (Li), tin (Sn), phosphorus (P), and sulfur (S) in an organic solvent; a drying step of removing the organic solvent from the homogeneous solution to obtain a precursor; A heat treatment step of heat-treating the precursor to obtain a sulfide-based solid electrolyte, the solution-forming step includes a solution-forming step 1 of preparing a Li-P-S homogeneous solution by mixing Li 2 S and P 2 S 5 in the organic solvent, and a solution-forming step 2 of preparing a Li-Sn-S homogeneous solution containing at least lithium (Li), tin (Sn), and sulfur (S) in the organic solvent; Mixing the Li-P-S homogeneous solution and the Li-Sn-S homogeneous solution to prepare a homogeneous solution; The method for producing a sulfide-based solid electrolyte, wherein the solution forming step 2 includes mixing Li 2 S, SnS, and S in the organic solvent to prepare a Li—Sn—S homogeneous solution.

2. A method for producing a homogeneous solution containing at least lithium (Li), tin (Sn), phosphorus (P), and sulfur (S) in an organic solvent, comprising: a drying step of removing the organic solvent from the homogeneous solution to obtain a precursor; A heat treatment step of heat-treating the precursor to obtain a sulfide-based solid electrolyte, The solution forming step comprises: 2 S and P 2 S 5 and a Li-P-S homogeneous solution is prepared by mixing the above in the organic solvent. A Li-Sn-S homogeneous solution is prepared by mixing the above in the organic solvent. 2 and a solution forming step 3 of mixing S and S in the organic solvent to prepare a Li—S homogeneous solution, A method for producing a sulfide-based solid electrolyte, comprising mixing the Li-P-S homogeneous solution, the Li-Sn-S homogeneous solution, and the Li-S homogeneous solution to prepare a homogeneous solution.

3. A method for producing a homogeneous solution containing at least lithium (Li), tin (Sn), phosphorus (P), and sulfur (S) in an organic solvent, comprising: a drying step of removing the organic solvent from the homogeneous solution to obtain a precursor; A heat treatment step of heat-treating the precursor to obtain a sulfide-based solid electrolyte, The solution forming step comprises: 2 S and P 2 S 5 and a Li-P-S homogeneous solution is prepared by mixing the above in the organic solvent. A Li-Sn-S homogeneous solution is prepared by mixing the above in the organic solvent. 2 The method includes a solution forming step 3 of preparing a Li-S homogeneous solution by mixing S and S in the organic solvent, and a solution forming step 4 of preparing a Li-Si-S homogeneous solution containing at least lithium (Li), silicon (Si), and sulfur (S) in the organic solvent, A method for producing a sulfide-based solid electrolyte, comprising mixing the Li-P-S homogeneous solution, the Li-Sn-S homogeneous solution, the Li-S homogeneous solution, and the Li-Si-S homogeneous solution to prepare a homogeneous solution.

4. The solution forming step 2 is 2 4. The method for producing a sulfide-based solid electrolyte according to claim 2, comprising preparing a Li—Sn—S homogeneous solution by mixing S, SnS, and S in the organic solvent.

5. The solution forming step 4 is 2 S, SiS 2 and S in the organic solvent to prepare a Li—Si—S homogeneous solution.

6. Li 3 P.S. 4 A slurrying step 1 for preparing a containing slurry liquid; a dissolution step of preparing a Li—Sn—S homogeneous solution containing at least lithium (Li), tin (Sn), and sulfur (S) in an organic solvent; The Li 3 P.S. 4 a slurrying step 2 of mixing the Li—Sn—S-containing slurry liquid and the Li—Sn—S homogeneous solution to prepare a mixed slurry liquid; a drying step of removing the organic solvent from the mixed slurry liquid to obtain a precursor; A heat treatment step of heat-treating the precursor to obtain a sulfide-based solid electrolyte, A method for producing a sulfide-based solid electrolyte, wherein the solution forming step includes adding and mixing Li 2 S, SnS, and S into the organic solvent to prepare a Li—Sn—S homogeneous solution.

7. The method for producing a sulfide-based solid electrolyte according to any one of claims 1 to 6, wherein the organic solvent is at least one selected from the group consisting of ether-based solvents, nitrile-based solvents, and ester-based solvents.

8. The method for producing a sulfide-based solid electrolyte according to any one of claims 1 to 7, wherein the organic solvent is at least one selected from the group consisting of tetrahydrofuran, acetonitrile, ethyl acetate, and methyl acetate.

9. The method for producing a sulfide-based solid electrolyte according to any one of claims 1 to 8, wherein the temperature in the drying step is 60 to 280°C.

10. The method for producing a sulfide-based solid electrolyte according to any one of claims 1 to 9, wherein the temperature in the heat treatment step is 200°C to 700°C.

11. 11. The method for producing a sulfide-based solid electrolyte according to claim 1, wherein the sulfide-based solid electrolyte contains an LGPS-based solid electrolyte and has peaks at least at 2θ=19.90°±0.50°, 20.20°±0.50°, 26.70°±0.50°, and 29.20°±0.50° in X-ray diffraction (CuKα: λ=1.5405 Å).

Citation Information

Patent Citations

  • Method for producing solid electrolyte

    JP2019169459A

  • Sulfide-based solid electrolyte material, battery, and process for producing sulfide-based solid electrolyte material

    WO2017002971A1

  • Sulfide solid electrolyte

    WO2017155119A1

  • Method for producing LGPS-based solid electrolyte

    WO2019044517A1

  • LGPS-based solid electrolyte and production method

    WO2019239949A1